Is there a better interceptive treatment for unerupted palatally displaced canines? A network meta-analysis - Viviane Zis de ARAUJO; Sani HECKMANN; Fernando Borba de ARAUJO; Luciano CASAGRANDE; Patricia Klarmann ZIEGELMANN; Eustáquio Afonso ARAÚJO; Leandro Silva MARQUES; Tathiane Larissa LENZI (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This systematic review aimed to investigate if there is a better interceptive treatment for palatally displaced canines (PDC) in the mixed dentition stage. The PubMed/MEDLINE, CENTRAL, Scopus, and EMBASE databases were searched for randomized clinical trials related to the research topic. The gray literature and reference lists were also assessed. Network meta-analysis was conducted to analyze the effects of different approaches on PDC eruption. The surface under the cumulative ranking area was calculated to rank the treatments. The certainty of the evidence was evaluated using the GRADE approach. Of the 892 eligible studies, 18 were selected for full-text analysis and 9 for meta-analysis, involving 506 participants and 730 PDC, to compare 9 approaches. The proportion of erupted PDC was significantly higher for all interceptive treatments compared with control (no intervention). Furthermore, the proportion of erupted PDC was higher in patients subjected to rapid maxillary expansion (RME) than those who underwent double extraction of primary canine and primary molar (relative risk (RR) = 2.68 ICr95%: 1.12-9.35). A higher proportion of erupted PDC was found for RME (RR = 3.07 ICr95%: 1.31-10.67), RME plus use of transpalatal arch (TA) plus extraction of primary canine(s) (EC) (RR = 1.43 ICr95%: 1.09-1.95), EC plus use of cervical pull headgear (RR = 1.38 ICr95%: 1.11-1.79), and EC plus use of TA (RR = 1.36 ICr95%: 1.00-1.9) than for EC. RME was most likely to be considered as the best interceptive treatment. Overall, the certainty of the evidence was considered low due to imprecision and indirectness. In conclusion, no intervention in the mixed dentition stage is the worst choice for PDC.